Two-sample Mendelian randomization analysis of the causal association between circulating inflammatory proteins and osteosarcoma - Hong Tang; Na Tang; Yueling Liao; Tao Tan; Hui Xie; Jiong Wang; Xie Hui (Discover Oncology)
Abstract Objective To investigate the causal relationship between 91 circulating inflammatory proteins and osteosarcoma using the two-sample Mendelian randomization method. Method Corresponding exposure and outcome data were extracted from genome-wide association study (GWAS) databases. A two-sample Mendelian randomization analysis was conducted on the data, with the inverse-variance weighted (IVW) method serving as the primary analytical approach. This was complemented by MR-Egger, weighted median, simple mode, and weighted mode methods to validate the results. Sensitivity analyses were also performed to verify the reliability of the data. Results The IVW analysis revealed a positive causal relationship between GCST90274776 (OR = 3.02, 95% CI: 0.033–0.117, P = 0.028), GCST90274822 (OR = 1.603, 95% CI: 1.014–2.535, P = 0.043), and GCST90274847 (OR = 2.580, 95% CI: 1.155–5.762, P = 0.021) and osteosarcoma. In contrast, GCST90274844 (OR = 0.313, 95% CI: 0.155–0.634, P = 0.001) showed a negative causal relationship with osteosarcoma. The supplementary analysis methods (MR-Egger, weighted median, simple mode, and weighted mode) consistently validated the direction and magnitude of these findings. The sensitivity analysis indicated that the data were reliable and free from bias. Conclusion Using the Mendelian randomization approach, this study suggest that GCST90274776, GCST90274822, and GCST90274847 may be risk factors for osteosarcoma, whereas GCST90274844 appears to exhibit a protective effect against the disease.